(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
As early as 1989 when it was clear that there was a possibility of unbanning liberation movements in South Africa and securing the release of political prisoners, the African National Congress (ANC)-aligned structures in the different townships began openly and radically mobilising for the organisation. The ANC-aligned demonstrations and protests became everyday scenes around the country and it was evident that the South African Police (SAP) was gradually battling to control the ANC-aligned citizens in most townships. In mid-1989, a gang known as the Three Million emerged in Maokeng Township (Kroonstad) and was accused by the community members to be operating as a vigilante group. Therefore, incidents of vigilantism by the Three Million Gang became a regular scene in this township. Using the Three Million as a case in point, I attempted to show how the ANC-aligned structures reacted to this gang which was viewed as a vigilante group in the Maokeng Township.